Geometrical size effect in the fatigue life predictions of aluminum wires with micro holes using methods of the critical distance. (15th March 2019) - Martínez, J.M.G.; Adriano, V.S.R.; Araújo, J.A.; Ferreira, J.L.A.; da Silva, C.R.M.
Highlights: S-N curves in aluminum alloy 6201-T81 wires, with and without geometric discontinuities. Fatigue life prediction using the LM (Nf ) relation and the uniaxial fatigue model. 3D approach in non-conventional geometries using the "focus path". Discussion of the effect of size on predicting fatigue life in wires with blind micro holes. Abstract: Recent research has shown that fretting fatigue is the main cause of fatigue failure in electrical transmission lines, and this phenomenon can be modeled as a stress concentration problem. The present study investigates the expected fatigue life of aluminum alloy 6201-T81 wires with micro holes, used in cables for transmission lines. The expected fatigue life of wires with micro holes is calculated based on the Theory of Critical Distances (TCD), where the characteristic size of the material ( LM ) varies with the number of cycles to failure ( Nf ), establishing an LM (Nf ) relation. To calibrate this relation, two S-N calibration curves were plotted with fully reversed uniaxial fatigue tests carried out on smooth wires (unnotched) and wires with a sharp notch. Experimental σ-N curves were constructed for different types of holes to validate and evaluate fatigue life prediction results of wires with micro holes, more precisely: ( i ) two through holes (TH), with diameters of 0.5 and 0.7 mm, and ( ii ) two types of blind holes (BH), with diameters and depths of 0.1 × 0.1 mm and 0.7 × 0.7 mm, respectively. The LM - Nf relation, based on the concepts of TCD, associated with the maximum principal stress as parameter to assess fatigue damage, was an effective methodology for fatigue life prediction of aluminum alloy 6201-T81 wires with micro holes.